Associations of Passive and Mentally Active Screen Time With Perceived School Performance of 197,439 Adolescents Across 38 Countries. - Khan, Asaduzzaman; Gomersall, Sjaan; Stylianou, Michalis (Academic Pediatrics, 2023)
OBJECTIVE: To examine the associations of passive (ie, television) and active (ie, electronic games, computer use) screen time (ST) with perceived school performance of adolescents across gender. METHODS: Data were from the 2014 Health Behaviour in School-aged Children survey conducted across 38 European countries and Canada. Perceived school performance was assessed using an item and dichotomized as high (good/very good) versus the remainder (average/below-average as reference). Participants reported hours per day of time spent watching television, playing electronic games, and using a computer in their free time. Multilevel logistic regression was used to estimate the associations. RESULTS: A total of 197,439 adolescents (average age 13.6 [standard deviation 1.63] years; 51% girls) were analyzed. Multivariable modeling showed that engaging in >2 h/d of ST was progressively and adversely associated with high performance in both boys and girls. Adolescents reporting >4 h/d of television time (≤1 h/d as reference) had 32% lower odds in boys (odds ratio [OR] 0.68; 95% confidence interval [CI]: 0.65-0.71) and 39% lower odds in girls (OR 0.61; 95% CI, 0.58-0.65) of reporting high performance. Playing electronic games for >4 h/d was associated with high performance with odds being 38% lower in boys (OR 0.62; 95% CI, 0.59-0.66) and 45% lower in girls (OR 0.55; 95% CI, 0.52-0.57). Sex differences in the estimates were mixed. CONCLUSIONS: High screen use, whether active or passive, was adversely associated with perceived high school performance, with association estimates being slightly stronger in girls than boys, and for mentally active than passive screen use. Discouraging high levels of screen use of any type could be beneficial to school performance.